ANALISIS TERHADAP KEKUATAN HUKUM INTERNASIONAL DALAM BIDANG EKONOMI DAN DAMPAKNYA TERHADAP KEDAULATAN NEGARA REPUBLIK INDONESIA - Muhammad Surya Nusantara Sandan; Sutiarnoto Sutiarnoto; Mahmul Siregar (Journal of USU International Law, 2020)
ABSTRACT Dr. Sutiarnoto, SH., M.Hum*) Dr. Mahmul Siregar, SH., M.Hum**) M. Surya Nusantara Sandan***) Sovereignty over territory or territorial sovereignty is the most important element of a country, and that sovereignty is what distinguishes a country from other subjects of international law. In forming an international law in the economic field, the agreement of rights and obligations that are formed can override the sovereignty of a country that approves it. The possibility of overruling sovereignty raises several issues that will be discussed in this thesis, namely: first what is sovereignty of the state in the view of international law, secondly how does the force bind of international law in the economic field and its impact on state sovereignty, and thirdly how is the standing of the Republic of Indonesia’s sovereignty in scope of international law that govern the field of international economics. The method used in this thesis is a normative descriptive legal research method. The data used as the source of this research are secondary data, obtained from research and analysis of written law and other literature reference materials related to state sovereignty and international law in the economic field. State sovereignty is recognized in international law as an authority to carry out law in its jurisdiction, to regulate the country's international relations activities, as well as to transfer ownership of a foreign property with specified compensation. However international law prohibits the use of national law to renege on the agreement. Civilized countries voluntarily respect that provision as a gesture of good faith. So does the Indonesian state, Indonesia was once bound by obligations in an agreement which turned out to worsen the national economic situation. Obligations carried out by Indonesia include, among others, the drafting of an Act that replaces the division system of duties and authority of state organs which is part of state sovereignty, permits the privatization of SOEs, and the termination of national projects that have the potential to compete in international environment. For those reason, there must be an obligation to protect the destruction of state for international economic law that applies to it, and be required more than enough understanding and preparation for countries that intend to agree on an international agreement in the economic field.    iiKeywords:     State Sovereignty, International Economic Law, Binding Force of International Treaties *) First Advisor of Faculty of Law, University of North Sumatra **) Second Advisor of Faculty of Law, University of North Sumatra ***) Student of International Law Department